Refugee Migration and Electoral Outcomes - Christian Dustmann; Kristine Vasiljeva; Anna Piil Damm (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
To estimate the causal effect of refugee migration on voting outcomes in parliamentary and municipal elections in Denmark, our study is the first that addresses the key problem of immigrant sorting by exploiting a policy that assigned refugee immigrants to municipalities on a quasi-random basis. We find that - in all but the most urban municipalities - allocation of larger refugee shares between electoral cycles leads to an increase in the vote share not only for parties with an anti-immigration agenda but also for centre-right parties, while the vote share for centre-left parties decreases. However, in the largest and most urban municipalities refugee allocation has - if anything - the opposite effect on vote shares for anti-immigration parties. We demonstrate response heterogeneity according to municipal characteristics, with a more pronounced response in less urban municipalities in which the pre-policy shares of both immigrants and the more affluent is high, and in urban municipalities with high unemployment. At the same time, higher pre-policy crime rates are associated with more support for anti-immigration parties in response to refugee allocation in both urban and non-urban municipalities. We also find some evidence that refugee allocation influences voter turnout. Moreover, it has a large impact on the decision of anti-immigration parties' choice of where to stand for municipal election.
Keywords: H53; I38; 330; immigration; political preferences; re-distribution; welfare; random allocation